A Structural Equation Model for Emerging Needs and Changing Role of Social Media Usage as Financial Service Platform - Shrikant Waghulkar, Prof.; Nitesh Behare, Dr; V .P Sriram, Dr; Anup Shivanacheri, Prof. (International Journal of Engineering and Technology, 2018)
In this Modern Era, the Major usage of social media is changing its old traditional mainstream from entertainment to the world of opportunity to work and trade. In the Emerging banking industry where customers' interaction plays a major and necessary role, Now a days, these digital communication is becoming a Predominant and strong communication channel between Customers and financial institutions. Digital Medias are considered as the most valuable tools for potential customers or clients get connected to the bank towards accessing their financial services in a most fashionable manner. Hence, the Emergence of Social Media as a major digital Platform which plays a major and replacing traditional way of getting financial services to a most modern way of accessing such financial services and its related information. In this paper, the researcher tries to portray the emerging importance of social media as a technological innovative platform which in turn plays a major role in Digital Banking and its related services. One way the researcher tries to bring the growing importance and need of these social media as innovative technological platform readily developing in banking sector where in customer could be able to access and do financial transactions in a most simpler and economical manner.Â
Keywords: Social Media; Financial Services; Digital Banking; Etc.